2018
DOI: 10.1155/2018/2570165
|View full text |Cite
|
Sign up to set email alerts
|

Channel Estimation and Peak‐to‐Average Power Ratio Analysis of Narrowband Internet of Things Uplink Systems

Abstract: Narrowband Internet of Things (NB-IoT) is a cellular based promising low-power wide-area network (LPWN) technology standardized by the 3rd Generation Partnership Project (3GPP) in release-13 as a part of the future 5th Generation (5G) wireless communication systems. The main design target of NB-IoT was to enhance radio coverage by repeating signal over an additional period of time for the ultralow-end IoT devices that would be operated in extreme coverage environments. But the power efficiency of the low-cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, the model is only efficient for linear data but not suitable for noisy or nonlinear data. In [99], two efficient narrowband demodulation reference signal (NDMRS)assisted channel estimation algorithms have been proposed. The NDMRS algorithms are based on the conventional least-squared (LS) [100], and minimum means square error (MMSE) [101] methods.…”
Section: Channel Estimation and Error Correctionmentioning
confidence: 99%
“…However, the model is only efficient for linear data but not suitable for noisy or nonlinear data. In [99], two efficient narrowband demodulation reference signal (NDMRS)assisted channel estimation algorithms have been proposed. The NDMRS algorithms are based on the conventional least-squared (LS) [100], and minimum means square error (MMSE) [101] methods.…”
Section: Channel Estimation and Error Correctionmentioning
confidence: 99%
“…The CE methods for NB-IoT can be categorized in two ways, namely frequency-domain and transform-domain. Frequency-domain CE approaches, particularly the least squares (LS) [11], [25], maximum likelihood (ML) [26], and linear minimum mean square error (LMMSE) [5], [12] estimators, can be used. The LS is the most straightforward CE approach among them but it exhibits severe performance degradation due to irreducible Gaussain distribution noise.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, the research related to channel estimation is inadequate since the NB-IoT system is still in its early stage of development for 5G IoT framework. Authors in [5] reported significant coverage performance improvement of uplink NB-IoT system by exploiting modified LS and LMMSE algorithms with considerable computational costs. Note that the NB-IoT supports only phase-shift keying modulation schemes [24].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations